2014
DOI: 10.1016/j.jpowsour.2014.04.120
|View full text |Cite
|
Sign up to set email alerts
|

Current density mapping and optical flow visualisation of a polymer electrolyte membrane water electrolyser

Abstract: A polymer electrolyte membrane water electrolyser (PEMWE) employing a segmented current collector made from a printed circuit board (PCB) with optical access to the channel has been demonstrated for the first time. The cell allows the local current density, flow regime and bubble formation dynamics to be studied in real time. Transition from bubbly to slug flow is observed towards the end of the channel under higher bubble formation conditions which is associated with a significant increase in local current de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 45 publications
(39 reference statements)
1
37
1
2
Order By: Relevance
“…In subsequent work using current density mapping, an increased current density was measured toward the channel outlet. 80 However, there is no comprehensive understanding of the current density distribution as van der Merwe et al 81 reported a decreasing current density along the channel, interpreted as a result of increasing oxygen gas to liquid water ratio. Such inconsistences might be explained by the differences in thermal boundary conditions, flow field or PTL structures.…”
Section: Transport Processes (2-phase)mentioning
confidence: 99%
“…In subsequent work using current density mapping, an increased current density was measured toward the channel outlet. 80 However, there is no comprehensive understanding of the current density distribution as van der Merwe et al 81 reported a decreasing current density along the channel, interpreted as a result of increasing oxygen gas to liquid water ratio. Such inconsistences might be explained by the differences in thermal boundary conditions, flow field or PTL structures.…”
Section: Transport Processes (2-phase)mentioning
confidence: 99%
“…Besides electrochemical characterization, optical imaging using transparent cell designs was conducted to investigate flow regimes and mass transport. Dedigema et al 16,17 showed that the transition of two-phase flow in the flow channel from bubbly to slug flow improves fluidic transport. Arbabi et al 18,19 characterized oxygen bubble growth based on microfluidic chips mimicking the bulk properties of a PTL.…”
mentioning
confidence: 99%
“…Experimental analyses with a 250 cm 2 circular and a 50 cm 2 square cell have shown that the contact pressure and the resulting interfacial contact resistances may result in heavily nonhomogeneous CDDs, which can lead to local temperature hot-spots and consequently enhance local degradation processes. Other works from Sun et al, 8 Dedigama et al 9 and one own recent work 10 focused on the operating conditions and their effects on temperature distribution and in particular on the CDD along the channel coordinate.…”
mentioning
confidence: 99%